ANALISIS TERHADAP HAK GUGAT DEBITUR PADA PELAKSANAAN LELANG EKSEKUSI DALAM PASAL 6 UNDANG-UNDANG NOMOR 4 TAHUN 1996 TENTANG HAK TANGGUNGAN ATAS TANAH BESERTA BENDA-BENDA YANG BERKAITAN DENGAN TANAH - Khoirul Muslihah (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2019)
The research aims to find out the causes and reasons for debtors to file a lawsuit or resistance to the auction process, and to analyze the decision of the Panel of Judges against the lawsuit / resistance submittedby the debtor against the auction conducted by KPKNL Malang based on Article 6 of the UUHT. The method used is normative juridical namely legal research conducted by examining and examining library materials.The results show that First, the emergence of a lawsuit by the debtor occurs due to several factors such as auction prices that are too low, the auction of bad loans carried out before the maturity of the credit agreement, procedures / procedures for conducting auctions that are not appropriate, for example, notification of auctions that are not timely , announcements that are not in accordance with procedures, related to inheritance and / or joint property issues for which the guarantee process is invalid, and for illegal acts in the auction process. Secondly, the decisions of judges in deciding auction cases vary, as is the case with the author, that there are decisions that win the KPKNL on the grounds that based on Article 6 of the UUHT the KPKNL has the authority to conduct an auction. Besides that there is also a decision canceling the auction because it did not meet the procedures.Key words: Debtor Claim Rights, Auction Implementation, UUHT